Experimental study of the potential use of diffusing wave spectroscopy to investigate the structural characteristics of blood under multiple scattering - Korolevich, Alexander N.; Meglinski, I. V. (Elsevier Science B.V., Amsterdam., 2000)
The extension of the photon correlation spectroscopy (PCS) in multiple scattering regime, so-called diffusing wave spectroscopy (DWS) was employed to the study of blood samples. Multiple scattered light from a helium–neon (He–Ne) laser beam incident on the blood samples was detected by a photomultiplier, and both the temporal autocorrelation intensity functions g2(τ) and power spectra S (w) were measured by a spectrum analyzer. The potentials of using DWS for the qualitative and quantitative determination of the structural characteristics of the blood elements were studied experimentally. The experimental studies made, permits the use of DWS for blood cells monitoring in a multiple scattering regime. This paper describes our initial attempts at applying DWS to the study of the discrete blood samples of both healthy donors and patients with the cardiac ischemia. The subsequent experiments provide a verification of DWS of blood cells shape monitoring under multiple scatte
Keywords: Diffusing wave spectroscopy; Blood; Multiple scattering; Temporal field autocorrelation function